Snapshot of Peptidomics of the Red Tide Forming Species Noctiluca scintillans - Zhang, Shuwen; Li, Cheng; Cheung, Shunyan; Sun, Mingming; Song, Shuqun; Guo, Wang; Guo, Cui; Wu, Gongguo; Liu, Hongbin (Frontiers in Marine Science, 2020)
The objective of this study was to investigate the peptidome of a red tide forming species Noctiluca scintillans based on mass-spectrometry (MS) analysis. N. scintillans cells were collected at the initiation and peak phases of its bloom. Peptides were extracted by ultrafiltration with cutoff of 10 and 3 kDa in acidic condition. Optimal mass spectra were generated after purification with C18 column. MS analysis and peptide identification was undertaken by Linear Trap Quadropole (LTQ) Velos MS/MS instrument. Using this method, 239 and 332 peptide sequences from the samples collected at the initiation and peak phases of N. scintillans bloom were identified, respectively. These sequences were classified and they were affiliated to 68 and 93 groups of precursor proteins, respectively, at the initiation and peak phases, with a compositional dissimilarity of 49.5%. Meanwhile, majority of the peptides were conjectured to come from contents digested by N. scintillans. Thirty-three groups of precursor proteins were detected at both phases. These peptides involved in various intracellular physiological activities, most of them responsible for functions of digestion activities such as oxidoreductase activity, catalytic activity, hydrolase activity and cofactor/ion binding. The compositions of precursor proteins, molecular weights, functions and cell compartments of the obtained peptides were quite different between two bloom stages. This is the first attempt to study peptidomics of N. scintillans, which provide important information on the functional studies of peptidomics in N. scintillans, especially food digestion and dietary protein utilization, as well as their relationship with bloom development.